RESEARCH METHODOLOGY OF PHONETICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines phonetic research methods, including the steps required to conduct a scientific investigation of speech sounds. It lists important procedures, such as establishing study goals, designing research projects, gathering and evaluating data, and guaranteeing validation. The article highlights a number of instruments and methodologies, including perceptual trials, articulatory imaging techniques, and sound analysis using software like Praat. Additionally, it highlights the importance of ethical considerations and interdisciplinary approaches in phonetic research. The results support applications in language learning, speech treatment, and speech technology